A combined heat source model for the prediction of residual stress post extreme high-speed laser material deposition. (June 2022) - Li, Tianci; Zhang, Lele; Chen, Geng; Pirch, Norbert; Schopphoven, Thomas; Gasser, Andres; Poprawe, Reinhart
Abstract: Extreme high-speed laser material deposition (EHLA) can be utilized for mass customization owing to its enhanced process speed and productivity. Although EHLA has multiple similarities with additive manufacturing techniques such as conventional laser metal deposition (LMD), the variation in the process speed causes different phase transformations and residual stress distributions. Therefore, a combined heat source model is proposed to evaluate the performance of structures repaired by EHLA and optimize process strategies. The model considers the unique energy input associated with the densification process compared with that of the conventionally used Gaussian heat source model. The parameters within the model were calibrated based on the residual stress distribution and molten pool morphology. The evolution of temperature and residual stress was investigated under various process conditions such as scanning speed and power input using the model. The consistency between the simulation and experimental results verified the viability of the model for determining EHLA parameters and improving the performance of repaired parts.